Acute effects of a single football training or match on passive hip rotation range of motion in semi-professional football players: A pilot study - De-la-Cruz-Torres, B.; Abuin-Porras, V.; Blanco-Morales, M.; De-la-Cueva-Reguera, M.; Calvo-Lobo, C.; López-López, D.; Romero-Morales, C. (Medicina, 2019)
Background and Objectives: The repetitive loading forces generated during football activities may induce alterations in the hip rotation range of motion (ROM) in players. The objective of this study was to evaluate the acute effects of a training and a match on bilateral passive hip rotation ROM in both lower limbs in soccer. Material and Methods: Twenty-eight male players were divided into two groups: 14 players (28 limbs) with normal bilateral hip rotation ROM (NH group) and 14 players (28 limbs) with restricted bilateral hip ROM (RH group). Passive bilateral hip rotation ROM was measured, by goniometer, before and after training or a match. Internal-rotation ROM (ROMIR), external-rotation ROM (ROMER), total ROM (ROMTOT) and relative internal rotation (ROMREL) were calculated. Results: The NH group did not show substantial changes in hip ROM after a training nor a match. After a training session, only the RH group exhibited a substantial increase in ROMIR, ROMER and ROMTOT. After a match, only the RH group exhibited a substantial increase in ROMER and ROMTOT and exhibited a substantial decrease in ROMREL. Comparing both groups, there were significant differences within ROM changes for ROMER and ROMTOT after training and for ROMER and ROMREL after a match. Conclusions: Despite the small sample size of the present study, the findings indicate that a single football activity leads to significant changes in hip rotation ROM in players with restricted bilateral hip external-rotation ROM. However, these changes did not reach reference cut-off scores.